Efektivitas Pelayanan Kesehatan Di UPTD Puskesmas Tengngalembang Kabupaten Sinjai - Sarina yanti; A. Djamaluddin; Mochamad Nurdin Idrus (Jurnal Ilmu Administrasi Negara, 2025)
This study aims to evaluate the effectiveness of health services at the Tenggalembang Community Health Center (UPTD) in Sinjai Regency. The method used was a qualitative approach with in-depth interviews and direct observation of health workers, the community, and program managers. The results showed that the main supporting factors for service success include timely service delivery, direct supervision by the head of the community health center, capacity building training for health workers, and collaboration with the BPJS (Social Security Agency) and village government. Services at the community health center were considered quite effective in terms of rapid treatment, availability of personnel and medicines, and increased community participation. However, there were obstacles such as low community participation due to busy schedules, shortages of medicines at the hamlet level, and limited access in remote areas. Although the JKN program and remote villages have helped reach communities in difficult areas, improvements in resource management, communication, and facilities are still needed to increase community satisfaction and trust in services. The conclusion of this study confirms that the effectiveness of health services at the Tengngalembang Community Health Center has been running well, but requires continuous improvement to ensure services are more optimal, efficient, and able to meet the needs of the community as a whole. The results of this study are expected to form the basis for developing strategies to improve community-based health services.